Life Cycle Assessment dan Life Cycle Cost untuk Serat Kenaf - Desrina Yusi Irawati; Melati Kurniawati (Universitas Katolik Parahyangan, 2020)
Kenaf fiber from the kenaf plant is the excellent raw material for industry because of the various diversified products it produces. To develop sustainable kenaf fiber, information is needed on the strengths and weaknesses of kenaf cultivation systems with respect to productivity and environmental impact. Therefore, a comprehensive environmental and economic impact assessment was conducted from cultivating kenaf to kenaf fiber. The environmental impact assessment uses the Life Cycle Assessment (LCA) method and economic calculations from the life cycle of kenaf to kenaf fiber to collectors use the Life Cycle Cost (LCC) method. The calculation of environmental impacts is in accordance with the stages of ISO 14040, using a single score assessment. The LCA results show that the treatment stage is the highest contributor of the three groups of impact categories. The highest to the lowest in the impact category group that was influenced by the treatment stage were resources with a value of 21.4 mPt, human health with a value of 8.76 mPt, and ecosystem quality with a value of 1.91 mPt. The cost identified through the LCC is Rp. 6,088,468,333, NVP and B/Cnet are positive. The results of the sensitivity analysis if there is a reduction in production> 6%, the business is still profitable and can be run.